Experimental study on screw connections in cold-formed steel walls with cement sheathing. Issue 9 (July 2019) - Abu-Hamd, Metwally
This article presents an experimental study on the screw connections between cold-formed steel walls and cement-based boards such as fibercement boards and ferrocement boards. The effect of loading direction, type of sheathing, board thickness, and screw number and spacing were investigated. Tests were performed under shear which is perpendicular to the free edge and also under shear which is parallel to the free edge of the board to simulate the actual behavior of sheathed shear walls. In each case, the peak load and displacement, elastic load and displacement, elastic stiffness and ductility were found and compared to other cases. The results of the 20 test reported in the paper showed that connection strength obtained under parallel loading was much higher than those obtained under perpendicular loading while as the displacements obtained under parallel loading were much larger than those obtained under perpendicular loading. Consequently, the elastic stiffness values were found to be smaller under parallel loading than under perpendicular loading. The results also showed that fibercement boards had much higher strength than ferrocement board, and that the screw strength increased nearly linearly with the board thickness.